Pengaruh Brand Identity terhadap Keputusan Pembelian Produk di Rabbani Bunker Rawamangun Jakarta Timur - Cyntia, Fani; Muhammad, Syuaiban (Program Studi Pendidikan Ekonomi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
The research objective is to learn the influence of Brand Identity (name, Logo, Color, packaging design, tagline and brand endorser, character, URL and website) against buying decision of Rabbani products in CV Rabbani Asyani at Rabbani Bunker Rawamangun. Normality test and homogeneity test applied before the main testing. Based on linear regression calculation, obtained Y= 46.32+0.575 (x) and ANAVA result shows Fcount <Ftable (0.473<1.94). Linier Shaped Fcount >Ftable ,(23,49>4,04) significan regression. Hypothesis testing done by calculating correlation Pearson Product and as result rxy=0.573, it shows that the brand identity affects Rabbaniâs product buying decision in at Rabbani Bunker Rawamangun is strong, related with interpretation criteria of the correlation coefficient Interpretation table.